Nutritional and Metabolic Consequences of Camelina Seed Oil Compared to Flaxseed Oil in a Rat Diet - Reshma Susan Babu; Adam Jurgoński (Molecules, 2025)
Camelina seeds are rich in α-linolenic acid (ALA), but also contain small amounts of erucic acid, which is considered toxic to laboratory rats. This experiment compares the dietary inclusion of camelina oil to that of flaxseed oil, a well-known source of ALA, and evaluates their effects on the nutritional and metabolic status of growing rats. The oils were chemically analyzed and incorporated into a semi-purified diet for 4 weeks. The experiment was divided into 3 groups: PO (control-fed palm oil with a trace of ALA), FO (comparative-fed flaxseed oil), and CO (experimental-fed camelina seed oil). Both CO and FO showed a higher percentage of lean body mass, greater lean mass gain, and a lower fat percentage compared to PO. Similar to the body composition, the blood lipid profile also improved in CO and FO, with higher HDL cholesterol and lower triglyceride levels, which was associated with upregulation of the peroxisome proliferator-activated receptor γ gene. However, in FO and CO, higher plasma liver enzyme activity and malondialdehyde concentrations were observed in the heart and liver. The results suggest that camelina oil has a similarly beneficial impact on the metabolic processes of the growing body as flaxseed oil, while also indicating a potential for increased organ-specific lipid peroxidation and hepatic burden when consumed in excess.